2022
DOI: 10.1007/s00592-022-02000-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Covid-19 on rates of gestational diabetes in a North American pandemic epicenter

Abstract: AimsWe assessed the impact of Covid-19 on gestational diabetes rates in Quebec, the pandemic epicenter of Canada. Methods We conducted a population-based study of 569,686 deliveries in Quebec between 2014 and 2021. We measured

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…11 Finally, meta-analyses of 438,548 pregnant patients found that severe COVID-19 infections were associated with gestational diabetes (OR 1.99; 95% CI: 1.09-3.64) at higher rates than patients with mild COIVD-19, but not compared to patients without COVID-19. 12 The pandemic may have also contributed to rates of gestational diabetes among pregnant women generally, 13,14 and increased rates during a lockdown period were also observed. 15 This latter observation may be due to indirect effects of the COVID-19 pandemic, including emotional distress, reduced physical activity, 15 reduced access to care, and reduced access to healthier nutrition, which may have contributed to increased rates of gestational diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…11 Finally, meta-analyses of 438,548 pregnant patients found that severe COVID-19 infections were associated with gestational diabetes (OR 1.99; 95% CI: 1.09-3.64) at higher rates than patients with mild COIVD-19, but not compared to patients without COVID-19. 12 The pandemic may have also contributed to rates of gestational diabetes among pregnant women generally, 13,14 and increased rates during a lockdown period were also observed. 15 This latter observation may be due to indirect effects of the COVID-19 pandemic, including emotional distress, reduced physical activity, 15 reduced access to care, and reduced access to healthier nutrition, which may have contributed to increased rates of gestational diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The possible increase in the prevalence of GDM during the pandemic may be due to several reasons, such as behavioral changes during lockdown, direct damage to pancreatic beta cells by the virus, or an infection-induced increase in insulin resistance. The following results can be derived from numerous studies on this question: ▪ GDM prevalence is increasing possibly associated with changes in screening procedures or lifestyle changes [57][58][59][60][61][62]; ▪ GDM prevalence does not change or is decreasing [63][64][65][66]; ▪ GDM is associated with a severe course of COVID-19 or insulin therapy [23,67]; ▪ Gestational weight gain (GWG) as a risk factor for GDM increases [68]. Taken together, from the existing literature there is some evidence that during the first two years of the pandemic and with low vaccination rate GDM prevalence increased locally, probably secondary to changes in lifestyle, such as less exercise, increasing BMI during lockdown, and GWG.…”
Section: Gdm Prevalence and Outcomes During The Pandemicmentioning
confidence: 99%
“…GDM prevalence is increasing possibly associated with changes in screening procedures or lifestyle changes 57 58 59 60 61 62 ;…”
Section: Introductionmentioning
confidence: 99%
“…Gestational diabetes mellitus (GDM) is one of the most common complications during pregnancy, and its prevalence has locally increased during the SARS-CoV-2 pandemic, associated with changes in lifestyle and modified GDM screening procedures. 1 Lockdown measures and restrictions of social gatherings reduced the amount of physical activity and favored sedentary behavior, leading to adverse effects on pregnancy in women with GDM, 2 such as excessive maternal gestational weight gain, worsening of glucose tolerance, 3 and preterm birth. 4 In addition, it is well known that increasing values from the oral glucose tolerance test (OGTT) are associated with increasing adverse perinatal outcomes.…”
Section: Introductionmentioning
confidence: 99%